Prenatal Aspiration of Fetal Ovarian Cysts: When to Intervene? A Case Report and Review of the Literature - Bonanni, Giulia; Shainker, Scott A.; Krispin, Eyal; Didier, Ryne A.; Buchmiller, Terry L.; Shamshirsaz, Alireza A. (American Journal of Perinatology Reports, 2025)
Fetal adnexal cysts present unique challenges during pregnancy, requiring careful management strategies to mitigate risks throughout gestation and delivery. We present the case of a 35-year-old G4P2 patient, referred to our center for a large adnexal cyst confirmed by ultrasound (US) and fetal MRI, with a calculated volume of 210 mL. Given the cyst's size and the family's strong preference for vaginal delivery (VD), US-guided aspiration was performed at 356/7 weeks, followed by an uncomplicated spontaneous VD at 372/7 weeks. Two weeks postpartum, the ovarian cyst re-accumulated, requiring laparoscopic-assisted cystectomy in a torsed but viable left ovary. This case demonstrates the importance of individualized prenatal care, where clinical decisions balance parental preferences with medical risks. Maximizing the opportunity for vaginal birth was a top priority for the family, and the successful reduction of the cyst's size through percutaneous aspiration minimized the risk of abdominal dystocia and allowed for a safe VD. We review relevant literature, emphasizing the need for further research to refine fetal intervention criteria and improve outcomes for such cases.
Keywords: fetal adnexal cyst; ultrasound-guided aspiration; fetal intervention; individualized prenatal care; prenatal diagnosis